Adaptation and initial validation of the Perceived Employability Scale - Monteiro, Sílvia (2019)
Our study seeks to (i) explore the factor structure of the perceived employability scale – Higher Education version; (ii) identify the biographical and contextual predictors of the perceived employability. For this purpose, 373 Portuguese graduates participated in our study. Based on collected data, we performed confirmatory factor analysis and regression analysis. The data allow to confirm a four-factor solution with a 67% total variance explained (34% for factor 1, 14% for factor 2, 12% for factor 3 and 7% for factor 4), based on the theorical framework. Regarding the predictors of the perceived employability, gender and study area arose as negative predictors, while the previous work experience showed to be a negative predictor. Based on the results we can provide theorical and practical explanations regarding the evaluation and intervention in the graduates’ employability.